KEANEKARAGAMAN JENIS VEGETASI TEGAKAN HUTAN PADA KAWASAN HUTAN KOTA BUKIT SENJA KECAMATAN SINGKAWANG TENGAH KOTA SINGKAWANG - Melaponty, Dwiagustien Putri; Fahrizal, .; Manurung, Togar Fernando (Universitas Tanjungpura, 2019)
The research was conducted in the Bukit Senja City Forest Area, Middle Singkawang Â District, Singkawang City. The purpose of the research was to find out diversity of forest vegetation in the city forest and vegetation which dominate the forest. The research was carried out for Â± 4 weeks in the field and continued to analysis data. Method used in the research is direct observation through the analysis of vegetation in the field by using a line of paved paths made in a direction perpendicular to the contour with 4 lines each path = 500m with lane 1 as many as 25 plots, lane 2 as many as 25 plots, lane 3 as many 19 plots and lanes 4 of 25 plots. Based on analysis on data there were dominant trees which filled the forest based on INP seed, namely Durian 78.828%, Karet 53.480% and Jelatung 22.81%. According to the type of tillers namely Karet 34.58%, Durian 26.02%, and Simpur 23.97%. From the quantitative analysis it showed that be seen that in the index value dominant Â (C) of a species is <1, which means the kind of go contained in the research is varies not only is controlled by one kind of. Diversity Type (H ') is in the group <1 which means it has a moderate Diversity Index (1 <H' <3). Abundant index (e) results show that the value of E => 0.6, which means that the type of abundant is high.Keywords: Bukit Senja Singkawang middle, City Forest, Vegetation Species Diversity